PHARMACOLOGICAL POTENTIAL OF MARINE ALGAE: A REVIEW - ALIEV , SARVAR; BADRIDDINOVICH, KOSIMOV KHUSNIDDIN; ALI , HASSAN MOHAMED; RAJENDRAN, C; TIWARI , MRS. POOJA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Microalgae, which include dinoflagellates, diatoms, and cyanobacteria, are unicellular, nearly microscopic organisms. In terms of organic production via photosynthesis, they are the main producers in the oceanic food web. Due to their multicellular nature, seaweeds and macroalgae occur on a macroscopic scale. In addition, seaweeds create extensive sub-marine forest habitats that provide refuge and food for marine life. Sargassum, Gracillariids, and kelps (Macrocystis, Laminaria) are a few examples. The high carbohydrate and bioactive content of the corresponding phylum has led to the commercial harvesting of macroalgae for use in food and medicinal manufacturing. Aquaculture can also benefit greatly from the use of marine algae. Microalgae are a common food source for fish, prawns, and bivalves that are crucial to the long-term viability of the aquaculture industry. Certain species are employed to improve larval eating, which raises the hatchery larvae's survival rate.